2020
DOI: 10.1136/bmj.m4075
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age and hospital admissions during childhood: population based, record linkage study in England (TIGAR study)

Abstract: ObjectiveTo examine the association between gestational age at birth and hospital admissions to age 10 years and how admission rates change throughout childhood.DesignPopulation based, record linkage, cohort study in England.SettingNHS hospitals in England, United Kingdom.Participants1 018 136 live, singleton births in NHS hospitals in England between January 2005 and December 2006.Main outcome measuresPrimary outcome was all inpatient hospital admissions from birth to age 10, death, or study end (March 2015);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 45 publications
1
40
1
Order By: Relevance
“…The risk of hospital admission associated with gestational age decreased over time, particularly after age 2; however, an excess risk remained up to age 10, even for children born at 38 and 39 weeks’ gestation. (3)…”
Section: Neonatal Lung Diseasesmentioning
confidence: 99%
“…The risk of hospital admission associated with gestational age decreased over time, particularly after age 2; however, an excess risk remained up to age 10, even for children born at 38 and 39 weeks’ gestation. (3)…”
Section: Neonatal Lung Diseasesmentioning
confidence: 99%
“…Results from a recent population-based record linkage study that we conducted—the TIGAR study [ 10 ]—indicated that children in England who were born preterm, and even those born a few weeks before their due date, were at a higher risk of hospital admissions throughout childhood than those born at term. Whilst the relationship decreased with time, there was an excess risk that persisted up to 7 to 10 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the relationship decreased with time, there was an excess risk that persisted up to 7 to 10 years of age. The study also showed that the majority of excess admissions experienced by children born before 40 weeks’ of gestation were attributed to infections [ 10 ]. However, it remains unclear which types of infection are most strongly associated with gestational age at birth and how these relationships may change with increasing age among children born in England.…”
Section: Introductionmentioning
confidence: 99%
“…The first large study to demonstrate this, published in 2012, used a cohort of 18,818 infants and found that individuals born between 37 and 38 weeks gestational age had a higher risk of adverse health and developmental outcomes at age 3 compared to those born between 39 and 41 weeks gestational age (Boyle et al, 2012). Subsequent studies have linked other phenotypes with early term birth, including higher risks of neonatal (Murzakanova et al, 2020) and later childhood illness (Coathup et al, 2020) and less favourable neurodevelopmental outcomes in early childhood (Hua et al, 2019; Rose et al, 2013).…”
Section: Introductionmentioning
confidence: 99%